Analysis of the Relationship Between Quality of Life and Fatigue in Individuals with Thalassemia Major - Ucar, Munevver; Tastan, Sevinc (Galenos Publ House, 2025)
Objective: Thalassemia major is a chronic blood disease that causes severe anemia. This causes individuals to feel fatigued and decreases their quality of life. This study aims to analyse the relationship between the QOL and fatigue in individuals with thalassemia major. Method: This study is a descriptive correlational study. This research was conducted in Nicosia, North Cyprus, with 78 individuals with thalassemia major. Data were collected using the personal information form, Nottingham health profile, and visual analogue fatigue scale. Results: The researcher calculated the average age of the participants as 38.9 +/- 7.23. The sub-dimension of the Nottingham Health Profile scale showed that emotional reaction, pain, and levels of energy were the lowest in the QOL of the participants with scores of 53.2, 52.6, and 51.2, respectively. The average score of the participants was 4.5 in the visual analog fatigue scale. There was a weak negative correlation (r=-0.241, p<0.034) between the visual analog fatigue scale scores and the total scores in the QOL scale, and a moderately negative correlation between the visual analog fatigue scale and the pain subscale scores (r=-0.475, p<0.01). Conclusion: The results of the study reveal the importance of planning health services to reduce fatigue and improve the QOL of patients with thalassemia major, as well as monitoring their fatigue levels and QOL.
Keywords: Thalassemia major; fatigue; quality of life